Virtual Museum and art education: Pedagogical Route for the dissemination of school art - Amado García, Jesús Alberto; Suárez Reyes, Mayerly Andrea; Bautista Villamizar, Ana María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
School museography is gaining ground in virtuality thanks to technology. So it is necessary to establish the pedagogical route for the creation of a virtual museum as a space for artistic dissemination of secondary education through the use of ICT. For this reason, from the creation research, a theoretical-practical method of artistic techniques is proposed for the generation of school art works and virtual online tools for the construction and network assembly of the 2D and 3D museographic proposal. As a result, the Virtual Museum of Salesian Art is created with more than 1,000 works.